2017
DOI: 10.1534/g3.117.043141
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Cycling Genomic Selection in a Multiparental Tropical Maize Population

Abstract: Genomic selection (GS) increases genetic gain by reducing the length of the selection cycle, as has been exemplified in maize using rapid cycling recombination of biparental populations. However, no results of GS applied to maize multi-parental populations have been reported so far. This study is the first to show realized genetic gains of rapid cycling genomic selection (RCGS) for four recombination cycles in a multi-parental tropical maize population. Eighteen elite tropical maize lines were intercrossed twi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
77
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(85 citation statements)
references
References 28 publications
6
77
2
Order By: Relevance
“…Recently, in tropical maize, by employing RCGS on eight bi-parental populations evaluated under drought stress environments, Beyene et al (2015) reported an average gain of 0.086 ton ha −1 per cycle, and hybrids derived from cycle 3 produced 7.3% (0.176 ton ha −1 ) higher grain yield than those from cycle 0 and conventional pedigree breeding methods. Further, Zhang et al (2017) using RCGS in a tropical maize multi-parental population reported a genetic gain for grain yield from cycle 1 to cycle 4 reached 0.225 ton ha −1 per cycle, which is equivalent to 0.100 ton ha −1 year −1 over a 4.5 year breeding period from the initial cross to the last cycle. While similar rates of gain have not been reported in legumes, recent reports on over three generations per year in traditional breeding for pigeonpea offer new opportunities to apply RCGS to accelerate rates of genetic gain in grain legumes.…”
Section: Rapid Cyclingmentioning
confidence: 97%
“…Recently, in tropical maize, by employing RCGS on eight bi-parental populations evaluated under drought stress environments, Beyene et al (2015) reported an average gain of 0.086 ton ha −1 per cycle, and hybrids derived from cycle 3 produced 7.3% (0.176 ton ha −1 ) higher grain yield than those from cycle 0 and conventional pedigree breeding methods. Further, Zhang et al (2017) using RCGS in a tropical maize multi-parental population reported a genetic gain for grain yield from cycle 1 to cycle 4 reached 0.225 ton ha −1 per cycle, which is equivalent to 0.100 ton ha −1 year −1 over a 4.5 year breeding period from the initial cross to the last cycle. While similar rates of gain have not been reported in legumes, recent reports on over three generations per year in traditional breeding for pigeonpea offer new opportunities to apply RCGS to accelerate rates of genetic gain in grain legumes.…”
Section: Rapid Cyclingmentioning
confidence: 97%
“…Fifteen elite tropical maize lines were crossed in diallelic fashion to form cycle 0 (C 0 ), which was genotyped using GBS markers and phenotyped at two locations in Mexico; plants with the best phenotype were selected to form the parents for GS cycle 1 (C 1 ). The C 1 parents were intercrossed and the progeny genotyped with the same GBS markers used for the C 0 population [73].…”
Section: Genetic Gains From Rapid Selection Cycle Gs: Cimmyt Maize Bimentioning
confidence: 99%
“…Bernardo and Yu [98] performed a simulation analysis in maize DH breeding and demonstrated that genome-wide selection has greater genetic advances than MAS. Subsequently, GS has been widely carried out in the study of maize inbred line selection, hybrid phenotypic and heterosis prediction, and has achieved great efficiencies in important agronomic traits, quality and yield of maize [99][100][101][102][103][104][105][106] . The prediction accuracy of GS is affected by multiple factors, such as the genetic structure of a trait, the number of markers, the size of the training population, and the kinship among individuals [107][108][109][110] .…”
Section: Molecular Breeding Methods In Plantsmentioning
confidence: 99%